Epidemiology of vulvar and vaginal cancer in Germany - Dittmer, C.; Katalinic, Alexander; Mundhenke, Christoph; Thill, M.; Fischer, D. (Archives of Gynecology and Obstetrics, 2011)
Objective: Vulvar and vaginal cancers are rare diseases with an incidence rate that increases with age. At present, epidemiological data are rather scarce. This review article provides an epidemiologic overview of these diseases, focussing on recent German data. Methods: This review article summarizes the information currently available in order to offer an epidemiologic overview. Results: The statistic incidence of vulvar carcinoma has been calculated between 2 and 7 cases per 100,000 women, and that of vaginal carcinoma 0.6-1.0 cases per 100,000 women. These incidence rates, especially concerning intraepithelial neoplasm, have increased heavily since the 1970s. The mean age of vulvar cancer affection is 72 years, and 74 years for vaginal carcinoma. In the case of women below the age of 50, cancer tends to be HPV-associated which implies a coincidence of about 20% for cervical and anal cancer. Various pathological mechanisms are the cause for women above the age of 50. Conclusions: Due to a change in sexual behavior and an increased rate of HPV infection among younger women, increased incidence of both diseases has to be expected. The age-standardized mortality rate of vulvar carcinoma in Europe is stated at 0.7/100,000 women, and that of vaginal carcinoma at 0.4/100.000 women. To what extent the HPV-vaccination affects incidence and mortality rates is continually being observed. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Epidemiology; Incidence; Mortality; Vaginal cancer; Vulvar cancer